Keck spectroscopy and NICMOS photometry of a redshift z=5.60 galaxy - Weymann, R; Stern, D; Bunker, A; Spinrad, H; Chaffee, F; Thompson, R; Storrie-Lombardi, L (Institute of Physics Publishing, 1998)
We present Keck Low Resolution Imaging Spectrometer spectroscopy along with Near-Infrared Camera and Multiobject Spectrometer (NICMOS) F110W (∼J) and F160W (∼H) images of the galaxy HDF 4-473.0 in the Hubble Deep Field (HDF), with a detection of an emission line consistent with Lyα at a redshift of z = 5.60. Attention to this object as a high-redshift galaxy was first drawn by Lanzetta, Yahil, and Fernandez-Soto and appeared in their initial list of galaxies with redshifts estimated from the Wide Field Planetary Camera 2 (WFPC2) HDF photometry. It was selected by us for spectroscopic observation, along with others in the HDF, on the basis of the NICMOS F110W and F160W and WFPC2 photometry. ForH0 = 65 km s-1 Mpc-1 and q0 = 0.125, the use of simple evolutionary models along with the F814W (∼I), F110W, and F160W magnitudes allow us to estimate the star formation rate (∼13 M⊙ yr-1). The colors suggest a reddening of E(B - V) ∼ 0.06. The measured flux in the Lyα line is approximately 1.0 × 10-17 ergs cm-2 s-1, and the rest-frame equivalent width, correcting for the absorption caused by intervening H I, is ∼90 Å. The galaxy is compact and regular, but resolved, with an observed FWHM of ∼0″.44. Simple evolutionary models can accurately reproduce the colors, and these models predict the Lyα flux to within a factor of 2. Using this object as a template shifted to higher redshifts, we calculate the magnitudes through the F814W and two NICMOS passbands for galaxies at redshifts 6 < z < 10. © 1998. The American Astronomical Socicly. All rights reserved.